Management Practices Affect Soil Nutrients and Bacterial Populations in Backgrounding Beef Feedlot. Issue 6 (1st November 2015) - Netthisinghe, A. M. P.; Cook, K. L.; Gilfillen, R. A.; Sistani, K. R.; Woosley, P. B.
Abstract : Contaminants associated with manure in animal production sites are of significant concern. Unless properly managed, manure‐derived soil nutrients in livestock production sites can deteriorate soil and water quality. This 3‐yr study evaluated a soil nutrient management strategy with four sequentially imposed management practices: 12‐mo backgrounding (BG), manure removal from the feeder area (FD), 12‐mo destocking (DS), and 12‐mo grass hay harvesting (H) in a small backgrounding feedlot. Resulting soil nutrient levels, total ( 16S‐rRNA ), and N cycling bacterial ( amoA and narG ) populations after each management practice in feedlot feeder and grazing (GR) areas and in crop grown at the control location (CT) were measured. Irrespective of management practice, FD contained greater soil nutrient concentrations than the GR and CT. Regardless of management practice, total bacteria cells (1.4 × 10 10 cells g −1 soil) and nitrate reducers (5.2 × 10 7 cells g −1 soil) were an order of magnitude higher in the FD than in the GR and CT, whereas nitrifying bacteria concentrations (1.4 × 10 7 cells g −1 soil) were higher in the GR. Manure removal from the feeder area reduced M3‐P (39%), total C (21%), total N (23%), NH4 –N (47%), and NO3 –N (93%) levels established in the FD during BG. Destocking lowered total C and N (45%) in the FD and NH4 –N (47%), NO3 –N (76%), and Zn (16%) in the GR. Hay harvesting reduced all soil nutrients in the FD and GR marginally. The management strategy has potential to lower soil nutrient concentrations, control soil nutrient buildup, and limit nutrient spread within the feedlot. Core Ideas: This study examined the effect of management practice on beef feedlot soil nutrients. Management strategy can prevent further soil nutrient build‐up and spread. Soil nutrient management strategy has the potential to lower environmental risks.